Analysis of Potential Hazards at Press Stations Using the Hazard and Operability Study (Hazop) Method at XYZ Palm Oil Mill - Azhar Basyir Rantawi; Ahdiat L Siregar; Hendra Saputra; Istianto Budhi Rahardja; Ayu Putri Rayhan (Jurnal Inotera, 2026)
A preventive approach in identifying potential hazards in satiun presses in palm oil mills is very important to prevent work accidents. This study aims to analyze potential hazards at press stations in palm oil mills using the Hazard and Operability Study (HAZOP) method, identify the causes and impacts of each potential hazard found, determine the level of risk based on the results of risk assessments, and prepare appropriate control recommendations as an effort to improve occupational safety and health in the mill environment. The results of the study showed that the level of risk at the press station varied from the Medium category (exposure to hot steam/oil and scratches on the work tools), High (slipping on the floor/slippery stairs and electric shock), to the Extreme category which is very critical in the form of the potential for workers' hands to be pinched on the screw press machineduring cleaning (possibility: 3, severity: 5). As an effort to improve work safety, integrated control recommendations were formulated which include the implementation of strict cleaning SOPs, the implementation of the Lockout/Tagout (LOTO) system on machines and electrical panels, housekeeping improvements with the installation of anti-slip step nosing materials, and the obligation to use standard PPE in a disciplined manner.